Robotic retroperitoneal lymph node dissection for testicular cancer at a national referral centre. Issue 5 (31st March 2022) - Grenabo Bergdahl, Anna; Månsson, Marianne; Holmberg, Göran; Fovaeus, Magnus
Abstract: Objectives: We aim to determine if robot‐assisted retroperitoneal lymph node dissection (R‐RPLND) can be performed as a safe option to open RPLND in selected patients with metastatic germ cell cancer. Patients and methods: This population‐based prospective study was performed at a one of two national referral centres for RPLND in Sweden. All patients referred during January 2017–March 2021 were screened for possible inclusion. R‐RPLND was performed using the Da Vinci Xi surgical system. Perioperative parameters, postoperative complications (Clavien–Dindo), final pathology, preservation of antegrade ejaculation and relapse rates were evaluated. Classifiers for selecting patients to open versus robotic RPLND were analysed by logistic regression modelling. The median follow‐up was 23 months. Results: Of 87 patients referred, 29 were selected for R‐RPLND, 19 in a post‐chemotherapy setting. In median, retroperitoneal tumour diameter was 18 mm, BMI 24 kg/m 2, operative time 433 min, estimated blood loss 50 ml and length of stay 3 days. One patient underwent open conversion due to failure to progress. Four patients had Clavien–Dindo grade 3 complications, of which three were chylous‐related. No in‐field recurrences occurred during follow‐up. Conclusion: This population‐based study suggests that R‐RPLND can be safely performed in at least one third of patients referred for an RPLND. A relatively high rate of lymph‐leakage may represent a potential drawback. Tumour size may be the most important discriminator when deciding on robotic versus open RPLND. Further studies with longer follow‐up are needed to validate the results.